Descriptive study of 158 traumatized by physical violence at the Hospital de Clínicas - Bañales, Cecilia; Henderson, Eduardo; Cepellini, Raúl; Müller, Augusto (Cirugía del Uruguay, 1997)
A retrospective study is carried out on 158 cases of trauma due to physical violence admitted to the Emergency Department at the Hospital de Clínicas between May 1995 and September 1996. The authors analyse epidemiology, paraclinic, treatments and mortality. This study will be used as hypotheses far future research.